1993
DOI: 10.3109/17453679308993656
|View full text |Cite
|
Sign up to set email alerts
|

Femoral remodeling after arthroplasty of the hip: Prospective randomized 5-year comparison of 120 cemented/uncemented cases of arthrosis

Abstract: We compared radiographically the femurs for 5 years after cemented (Landos Titane) and uncemented (Zweymüller/Endler) hip arthroplasty (THA) for coxarthrosis in 120 patients. The bone changes followed a characteristic time-course with rapid initial remodeling and almost no further changes after 3-4 years. No association between bone changes and clinical results was found. The groups did not differ in bone atrophy and ectopic bone formation, whereas the incidence of distal cortical hypertrophy and proximal radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
3
8
0
3
Order By: Relevance
“…Radiolucent lines were defined as radiopaque lines of [ 1 mm adjacent to the implant and areas of osteolysis were defined as localized bone resorption and described according to Gruen et al [19]. Bone hypertrophy was defined as thickening of the distal periprosthetic diaphyseal bone of more than 2 mm on anteroposterior radiographs compared to postoperative radiographs [39]. Osteolysis was defined as areas of localized bone resorption or endosteal erosion [52].…”
Section: Methodsmentioning
confidence: 99%
“…Radiolucent lines were defined as radiopaque lines of [ 1 mm adjacent to the implant and areas of osteolysis were defined as localized bone resorption and described according to Gruen et al [19]. Bone hypertrophy was defined as thickening of the distal periprosthetic diaphyseal bone of more than 2 mm on anteroposterior radiographs compared to postoperative radiographs [39]. Osteolysis was defined as areas of localized bone resorption or endosteal erosion [52].…”
Section: Methodsmentioning
confidence: 99%
“…26,30,34,40 Among these studies, 3 randomised comparative studies showed the same conclusions: namely, there is no significant difference between cemented and uncemented THR with regard to the prevalence of HO. 16,34,41 The same finding also came from 2 matched pair comparisons 40,53 and 2 comparative studies in the same patient. 14,23 However, different findings were reported in 2 non-randomised comparisons.…”
Section: Radiological Evaluationmentioning
confidence: 61%
“…In addition, a matched pair subgroup was included in the 2 studies. Therefore, there were 12 publications in category N, 4,6,15,19,22,26,29,30,31,51,54,56 10 in category R, 11,16,24,33,34,36,41,45,46,55 5 in category M, 4,10,29,40,53 and 4 in category S. 14,21,23,44 The mean postoperative follow-up period ranged from one year to 9.3 years. Among all these studies, one was designed to compare cemented, porous-coated, and hydroxyapatite-coated THR 16 ; one was to compare cemented, uncemented, and hybrid THR.…”
Section: Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Bei Durchsicht der Röntgenbilder mit durchschnittlich 11 jährigem Verlauf waren 9 Hüften (31 %) massiv gelockert und weitere 11 Hüften (38 %) wiesen Säume gröûer als 2 mm in mehr als 2 Zonen auf. Es zeigte sich jedoch, unabhängig von der ¾tiologie, ein deutlicher Zusammenhang zwischen dem Parameter ¹Pfannenwanderungª (gemessen an dem Vergleich der unmittel- [5,10]. Manche Autoren diskutieren gerne einen gewissen ¹Setzeffektª zementfreier Pfannen in der ersten Zeit nach der Implantation, die dann zur Ruhe kommen und somit keine Pfannenlockerung darstellen.…”
Section: Introductionunclassified